The concept of ghulūw in Islam: an analysis on its manifestations and causes in the modern world - Md Yusoff, Muhammad Yusri Yubhi; Ushama, Thameem; Abdul Rahim, Adibah (International Islamic University Malaysia, 2020)
Ghulūw (Religious extremism) is an ongoing issue which has been debated from the past and continues to the present day. It is astounding how something associated with religion can lead a person far from religion for doing something that is forbidden itself. Therefore, to understand the reality of this concept of ghulūw in this modern world, this article will attempt to explore the meaning of ghulūw; firstly, from the etymological and linguistic points of view, and then secondly, from the perspective of sharaʿ including the Qur’ānic and Prophetic traditions before concluding its actual meaning by examining the opinions of both classical and contemporary Muslim scholars. Finally, this article will investigate its manifestations and causes of ghulūw in the modern world from the standpoint of contemporary Muslim scholars. Consequently, the study concludes that ghulūw refers to strictness in beliefs and actions which exceeds beyond the required limits of sharaʿ and therefore emphasizing the importance of embracing the characteristics of wasaṭiyyah as a remedy to reject and oppose all kinds of ghulūw.